Psychology - Gray, Peter (Worth Publishers, 2011)
More than ever, the new edition of Gray’s Psychology helps students understand the basic interactions between behavioral and biological science. Experience teacher and author…Cutting-edge researcher on the topic of evolutionary play…Psychology Today blogger…This combination makes Peter Gray the ideal author for a challenging yet accessible introduction to the fundamental questions explored by psychology researchers.